Biobank of Psychiatric Diseases Mannheim – BioPsy. (8th July 2016) - Witt, Stephanie; Dukal, Helene; Hohmeyer, Christine; Radosavljevic-Bjelic, Slavica; Schendel, Darja; Frank, Josef; Lang, Maren; Streit, Fabian; Strohmaier, Jana; Treutlein, Jens; Rietschel, Marcella
High quality biomaterial from patients and controls is a core prerequisite for research into the biological causes of mental disorder. BioPsy is the biobank of the Department of Genetic Epidemiology in Psychiatry at the Central Institute of Mental Health in Mannheim, Germany, and one of the largest psychiatric disorder biobanks worldwide. Here, ongoing collection is in progress for blood, DNA, mRNA, plasma, serum, saliva, urine, hair, and other biomaterials. Reuse of samples is permitted in a collaboration-based context. BioPsy operates according to German and European quality and data privacy standards.